The Effects of Artificial Intelligence on Implementors' Fidelity of Instructional Strategies During Handwashing Acquisition in Children with Autism. - Griffen, Brenna; Lorah, Elizabeth R.; Caldwell, Nicolette; Hantula, Donald A.; Nosek, John; Tincani, Matt; Lemley, Shea (Journal of Developmental & Physical Disabilities, 2024)
Handwashing is a vital skill for maintaining health and hygiene. For individuals with intellectual and developmental disabilities (IDD), such as autism spectrum disorder, evidence-based strategies, such as prompting and task analysis, may be effective in teaching these skills. Due to the shortage of experts who teach individuals with IDD skills such as handwashing, staff working with children need a means of ensuring these instructional strategies are implemented with fidelity. This study examined the effects of a tablet-based application that used artificial intelligence (GAINS®) on four behavior technicians' implementation of least-to-most prompting, total task chaining, and time delay during an acquisition of handwashing program with young children with autism. All four technicians increased fidelity immediately upon using GAINS and all four technicians reached mastery criteria within the shortest number of sessions possible. One child participant met mastery criteria, two showed some gains, and one demonstrated a high degree of variability across sessions. Limitations of the least-to-most prompting procedure, user design, considerations and directions for future research and practice are discussed.